La estructura práctica de la acción educativa. Esbozo de un campo de investigación - Bárcena Orbe, Fernando (Teoría de la Educación. Revista Interuniversitaria, 2009)
In this paper, the author attempts to show the essentialy contested character of the concept of education. Frecuently, education has been presented as a human practical action. However, in many contexts this thesis has been employed to elaborate a reflective and ethical perspective of educational profesión, as an alternative approach to a technological one, or, to the contrary, to justify the primacy of technological rationality on moral rationality in the educational process. In order to achieve a holistic perspective of education, both claims must be avoided. Concretely, the author propose to make up the tradition of practical philosophy, in which technical and ethical dimension of human action shaping a practical structure particularly linked with forms of practical cognition. In addition to this, the paper attempts to check some of the most important contributions in this field of educational research.